Analisis Sifat Mekanik dan Karakteristik Fisik Campuran Hidroksiapatit dari Tulang Sapi, Silika dengan Pengikat Resin sebagai Kandidat Implan Tulang - Yanda, Hengki Ebitra; Gunawarman, Gunawarman; Affi, Jon; Yetri, Yuli (Politeknik Negeri Padang, 2024)
Ceramic biomaterials based on hydroxyapatite (HA) and silica have been extensively studied due to their load-bearing capabilities in bone replacement and reconstruction applications. This study presents an analysis of the mechanical properties and physical characteristics of a mixture of bovine bone hydroxyapatite and silica with a resin binder as a candidate for bone implants. the objective of this research is to examine the effect of the quantity of hydroxyapatite grains and the composition of silica reinforcement particles on the mechanical and physical properties of the product. The methodology involves mixing bovine bone hydroxyapatite and silica in ratios of 90:10, 80:20, and 70:30. Subsequently, the specimens were molded and subjected to tensile tests to determine their tensile strength and elongation. Surface morphology analysis was conducted using a scanning electron microscope (SEM), while functional group and crystallographic analyses were performed using FTIR and XRD. the results indicate that the 70:30 composition provided the best outcomes, with a tensile strength of 13.07 MPa, compared to the 90:10 and 80:20 compositions, which had tensile strengths of 6.68 MPa and 12.96 MPa, respectively. The microstructure of the surface after tensile testing shows that the addition of silica can increase mechanical strength and reduce the porosity of the specimen surface.